Healthcare costs for allergic rhinitis patients on allergy immunotherapy: a retrospective observational study. (2nd November 2017) - Allen-Ramey, Felicia; Mao, Jianbin; Blauer-Peterson, Cori; Rock, Marvin; Nathan, Robert; Halpern, Rachel
Abstract: Objective: Subcutaneous immunotherapy (SCIT) for allergic rhinitis (AR) has been shown to control symptoms for up to several years following treatment discontinuation, but the effect of SCIT on healthcare costs for commercially insured patients is unknown. The objective of this study was to compare healthcare costs and resource utilization for patients with AR who received SCIT compared with those who discontinued SCIT shortly after initiation. Methods: This retrospective cohort study evaluated medical and pharmacy claims from the Optum Research Database from January 2009 through February 2014 for adults and pediatric patients with >7 (continuers) vs. ≤7 (discontinuers) injection visits for SCIT within 60 days of initiation. Results: After 1:1 propensity score matching, each cohort included 6710 patients. Continuers were less likely than discontinuers to use oral corticosteroids (27.7% vs. 29.6%, p = .018), or to have ≥1 respiratory-related emergency room visit (5.4% vs. 6.5%, p = .008) and ≥1 inpatient stay (1.1% vs. 1.7%; p = .002). Continuers were more likely than discontinuers to have ≥1 AR-related office (98.8% vs. 94.6%, p < .001) or outpatient visit (2.4% vs. 1.7%, p = .002). Continuers had greater mean total AR-related costs than discontinuers (1918 vs. 646, p < .001). Unadjusted mean total respiratory-related costs were lower for continuers than discontinuers, although the difference was not statistically significant (1589 vs. 1785, p = .077); when adjusted with a generalized linear model, these costs were significantly lower among continuers ( p < .001). Conclusions: Continued SCIT use is associated with decreased emergency room visits and inpatient stays, decreased oral corticosteroid use, and lower respiratory-related costs, compared with early discontinuation.